2015
DOI: 10.1590/01000683rbcs20140655
|View full text |Cite
|
Sign up to set email alerts
|

Influência da Matéria Orgânica no Diâmetro Médio de Minerais da Fração Argila de Solos Desenvolvidos de Basalto no Sul do Brasil

Abstract: resuMO a interação de compostos orgânicos com minerais de argila pode alterar o tamanho dos cristais. no entanto, em solos, esse efeito é ainda pouco claro por causa das limitações na separação de fases puras de minerais para realizar experimentos de dissolução. neste estudo, a relação entre a matéria orgânica do solo (MOs) e diâmetro médio do cristal (dMC) de minerais de argila de horizontes superficiais e subsuperfíciais de solos de uma topossequência no sul do Brasil foi avaliada. Os teores de C e n foram d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
7
0
6
Order By: Relevance
“…In contrast, a significant positive correlation was observed between the RI 1075 variation and the Fed content (R 2 = 0.97 and p<0.05), suggesting that the labile and polar structures of HU are stabilized by organo-mineral interactions. The interaction between sugars and Fe and Al oxides has also been observed by other authors (Schöning et al, 2005;Hanke et al, 2015). In the same soil, HA showed higher RIs of the carboxylic (RI 1710 ) and aromatic (RI 1630 ) groups, as well as higher AI values (Table 3).…”
Section: Chemical Composition Of Som Fractions By Ftirsupporting
confidence: 82%
“…In contrast, a significant positive correlation was observed between the RI 1075 variation and the Fed content (R 2 = 0.97 and p<0.05), suggesting that the labile and polar structures of HU are stabilized by organo-mineral interactions. The interaction between sugars and Fe and Al oxides has also been observed by other authors (Schöning et al, 2005;Hanke et al, 2015). In the same soil, HA showed higher RIs of the carboxylic (RI 1710 ) and aromatic (RI 1630 ) groups, as well as higher AI values (Table 3).…”
Section: Chemical Composition Of Som Fractions By Ftirsupporting
confidence: 82%
“…For the TR, the MCD of both Gt and Hm was also inversely related to the increase in residue rates applied in the surface layer. The data of Hanke et al (2015) showed that the MCD of Gt, Hm, and Kt can be affected by a higher OM content in the soil surface layer, so that the diameter is often reduced, due to the interactions between the mineral and the medium, reducing the crystallinity and increasing reactivity. Also in the TR, IS in Gt was not clearly related with increasing residue rates and soil OM.…”
Section: Discussionmentioning
confidence: 99%
“…The SOM effect on aggregation has traditionally been attributed to the inner sphere complexes between the carboxyl groups and cations of the mineral structure by the ligand exchange mechanism (Chorover and Amistadi, 2001;Mikutta et al, 2011). Others types of organo-mineral interactions are also proposed: i) hydrophobic interactions; ii) C-O-alkyl groups and mineral hydroxyls; iii) cation bridges; iv) anion and cation exchange; and v) Van der Waals interactions (Stumm, 1992;Dick et al, 2009;Hanke et al, 2015). However, the effects of these organo-mineral interactions on aggregate stability have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%